Direct optical micropatterning of poly(dimethylsiloxane) for microfluidic devices. (7th June 2018) - Gao, Shaorui; Tung, Wing-Tai; Wong, Dexter Siu-Hong; Bian, Liming; Zhang, A Ping
Abstract: Poly(dimethylsiloxane) (PDMS) is one of the most popular polymer materials for microfluidic devices. However, it still remains a challenge to rapidly fabricate PDMS microfluidic devices with micrometer-scale feature sizes. In this paper, we present gray-scale digital photolithography technology for direct patterning of large-area high-resolution PDMS microstructures for biomicrofluidic applications. With the positive- and negative-tone photosensitive PDMS (photoPDMS), we rapidly fabricated various PDMS microstructures with complex geometries by using a one-step patterning process. The positive-tone PDMS was used to pattern large-area microfluidic chips, while the negative-tone PDMS was utilized to fabricate high-resolution on-chip microstructures and components. In particular, a large-area microfluidic chip of 5.5  ×  2.8 cm 2 with complex three-dimensional (3D) staggered herringbone mixers was fabricated from the positive-tone PDMS by using a single-step optical exposure process; a small microfluidic chip with a feature size as small as 5 µ m was prepared with the negative-tone PDMS. Furthermore, 3D surface engineering of PDMS microchannels was demonstrated to customize extracellular microenvironments for investigating cell migration.